Effectiveness of pedagogic praxes in teaching matter and kinetic molecular theory at grade 10 in selected schools in the Mthonjaneni circuit in South Africa - Eric, Danso; Mngomezulu, Thanduxolo Peace TP.; Mpuangnan, Kofi N (Edelweiss Applied Science and Technology, 2025)
When teaching physical sciences, practical methods are crucial for fostering students’ conceptual knowledge and practical abilities. The impact of the Practical Investigative Learning (PIL) approach on Grade 10 students’ understanding of Matter and the Kinetic Molecular Theory (M-KMT) was investigated in this study. Using a positivist-based quasi-experimental design, a pre-test and a post-test were included. 50 Grade 10 students from two high schools in KwaZulu-Natal’s Mthonjaneni circuit were chosen at random. 25 students from the experimental group attended a school with a fully functional science lab, whereas 25 students from the control group attended a school without a laboratory. The experimental group received instruction through PIL, while the control group received traditional instruction from the same qualified physical sciences teacher. An independent t-test (p > 0.05) was used to compare the results of the pre-test and post-test after descriptive statistics were applied. The results show that learners’ conceptual understanding of M-KMT was greatly improved by the PIL approach, which made abstract ideas more concrete and understandable.